Comparisons of depression, anxiety, well-being, and perceptions of the built environment amongst adults seeking social, intermediate and market-rent accommodation in the former London Olympic Athletes' Village. (November 2017) - Ram, Bina; Shankar, Aparna; Nightingale, Claire M.; Giles-Corti, Billie; Ellaway, Anne; Cooper, Ashley R.; Page, Angie; Cummins, Steven; Lewis, Daniel; Whincup, Peter H.; Cook, Derek G.; Rudnicka, Alicja R.; et al.
Abstract: The Examining Neighbourhood Activities in Built Living Environments in London (ENABLE London) study provides a unique opportunity to examine differences in mental health and well-being amongst adults seeking social, intermediate (affordable rent), and market-rent housing in a purpose built neighbourhood (East Village, the former London 2012 Olympic Athletes' Village), specifically designed to encourage positive health behaviours. Multi-level logistic regression models examined baseline differences in levels of depression, anxiety and well-being across the housing groups. Compared with the intermediate group, those seeking social housing were more likely to be depressed, anxious and had poorer well-being after adjustment for demographic and health status variables. Further adjustments for neighbourhood perceptions suggest that compared with the intermediate group, perceived neighbourhood characteristics may be an important determinant of depression amongst those seeking social housing, and lower levels of happiness the previous day amongst those seeking market-rent housing. These findings add to the extensive literature on inequalities in health, and provide a strong basis for future longitudinal work that will examine change in depression, anxiety and well-being after moving into East Village, where those seeking social housing potentially have the most to gain. Highlights: A natural experiment examining baseline mental health and well-being in adults seeking three housing tenures in East Village. Those seeking social housing are more likely to report depressive symptoms and low life satisfaction at baseline. Differences in well-being outcomes across the housing groups can be partially explained by neighbourhood perceptions. Those seeking social housing appear to have the most to gain by moving to East Village.